Human monkeypox coinfection with syphilis in an immunocompromised patient (Dermatology Reports, 2022)
Monkeypox is a viral zoonosis from the Poxviridae family that spreads at an unprecedented rate. It is transmitted through contact with skin lesions, respiratory droplets, body fluids, and sexual contact. The diverse presentation of the disease leads to misdiagnosis. Thus, clinicians should have a high index of suspicion, mainly with diseases with skin lesions. The most vulnerable group to developing this disease are individuals with risky sexual relationships, sexually transmitted infections, or human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). To date, only one case of coinfection with the monkeypox virus, syphilis, and HIV has been reported; however, no cases have been revealed in the Mexican territory. Herein we describe an unusual case of syphilis-monkeypox coinfection in an immunocompromised patient; despite his coinfection, he had a favorable prognosis. Furthermore, we attach allusive pictures of the natural evolution of dermatological lesions.